The Impact of Cloud Computing on the Quality of Accounting Information in Libyan Commercial Banks (A Field Study) (Comprehensive Journal of Science, 2026)
​This study aimed to identify the impact of cloud accounting on improving the quality of accounting information in Libyan commercial banks, in light of the rapid digital transformation witnessed by the banking sector and the resulting requirements related to efficiency, accuracy, and speed in providing accounting information to support decision-making. The study originated from a problem concerning the extent to which cloud accounting techniques contribute to enhancing the qualitative characteristics of accounting information, particularly relevance, reliability, accuracy, and timeliness.​The study relied on the descriptive-analytical approach and used a questionnaire as the primary tool for data collection from a sample of (34 individuals) among employees in accounting departments and information systems in several branches of Libyan commercial banks operating in the municipalities of Gharyan and Yefren. Data were analyzed using appropriate statistical methods to test the study's hypotheses.​The results reached a statistically significant impact of using cloud accounting on the quality of accounting information. These technologies contribute to improving data processing speed, reducing errors, and increasing the degree of reliance on accounting information in making administrative and financial decisions. The results also showed that the level of cloud accounting adoption still faces some challenges related to technical infrastructure and information security.The study recommended the necessity of enhancing investment in cloud computing technologies, establishing clear information security policies, and training accounting and technical staff. This would reflect positively on the quality of accounting information and support performance efficiency in Libyan commercial banks.
Keywords: Cloud Computing, Quality of Accounting Information, Accounting Information Systems, Libyan Commercial Banks